2015
DOI: 10.1158/0008-5472.can-14-1924
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase Is Regulated by β-Catenin/TCF and Promotes Radioresistance in Prostate Cancer Progenitor Cells

Abstract: Radiotherapy is a curative treatment option in prostate cancer. Nevertheless, patients with high-risk prostate cancer are prone to relapse. Identification of the predictive biomarkers and molecular mechanisms of radioresistance bears promise to improve cancer therapies. In this study, we show that aldehyde dehydrogenase (ALDH) activity is indicative of radioresistant prostate progenitor cells with an enhanced DNA repair capacity and activation of epithelial-mesenchymal transition (EMT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
252
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 207 publications
(279 citation statements)
references
References 50 publications
24
252
0
3
Order By: Relevance
“…[28][29][30] The Wnt signaling pathway is one of the important signaling pathways for maintaining stemness. 31,32 Therefore, we tried to determine whether CONPs can influence Wnt signaling. Western blot and qRT-PCR results indicated that CONPs can inhibit the expression of genes involved in Wnt signaling such as Wnt1A, FZD7, c-Myc, and Cyclin-D1, which can explain why CONPs can attenuate the stemness of prostate cancer cells and cause cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The Wnt signaling pathway is one of the important signaling pathways for maintaining stemness. 31,32 Therefore, we tried to determine whether CONPs can influence Wnt signaling. Western blot and qRT-PCR results indicated that CONPs can inhibit the expression of genes involved in Wnt signaling such as Wnt1A, FZD7, c-Myc, and Cyclin-D1, which can explain why CONPs can attenuate the stemness of prostate cancer cells and cause cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Many ALDHs have been implicated in stem cell regulation where ALDH-dependent RA signaling is involved in gene expression and morphogenesis and is crucial for normal development ( Figure 2) (6,(12)(13)(14). In a recent study which is the focus of this perspective, Cojoc et al (15) examined the regulation of ALDH in prostate cancer stem cells (PCSCs) and its role in prostate tumor radioresistance. One of the major factors contributing to prostate cancer patient mortality is relapse following radiotherapy (16); therefore, it is crucial to identify the mechanisms that surviving cells, presumably CSCs, utilize to evade this lethal treatment and reestablish the tumor.…”
Section: Figurementioning
confidence: 99%
“…In order to identify genes expressed in tumor PCSCs, these cells were enriched for and isolated from a mouse xenograft tumor and genome expression analyzed (15). These cells showed a correlation between CD44+/CD133+ PCSCs and levels of ALDH1A1, ALDH3A1, ALDH3B1, and ALDH6A1; with ALDH1A1 and ALDH6A1 also being significantly enriched in prostate carcinomas compared to normal prostate tissue.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations